BENTUK BAHASA LISAN YANG TERDAPAT PADA STATUS FACEBOOK ORANG JEPANG - Learosiana '; Hana Nimashita Nimashita; Arza Aibonotika Aibonotika (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The purposes of this research is to determine which particle is the most deleted and how changes in word word order on Japanese’s facebook status and what affect of changes inword order. The objects of this research is the deleted particle and changes in word order on Japanese’s facebook status which are posted on facebook. This research is descriptive qualitative which is interpret the object based on theory. The data of this research are collected by reading status posted on facebook, that status contains the deleted particle changes in word order, then it is arranged by written technique. Theory in analyzing the data of this research is theoretical form of spoken language based on Tomisaka (1996) and Seiichi Makino theory, and use praat aplication to know intonation effect in the improvement of word order. The result of this research shows the most deleted particle on Japanese’s facebook status is particleを(wo) and changes in word order on Japanese’s facebook status is higher intonation to focus the sentence element. Hope this research with larger number need to be done, so that the result of this research can be generalized.Keyword: Deleted particle, changes in word order, Facebook